Coumarin hybrids: dual-target candidates for future antimicrobial and antitubercular therapies - Bavishi, Abhay; Vala, Hardev; Thakrar, Shailesh; Swami, Sagar; Sarkar, Dhiman; Shukla, Rushit; Kamdar, Jignesh; Shah, Anamik (Future Medicinal Chemistry, 2025)
Aims: This study aimed to synthesize, characterize, and evaluate the antimicrobial and antitubercular activities of two novel series of coumarin-based derivatives (Series 5 and Series 9), focusing on their structure-activity relationship (SAR) and molecular docking interactions with key bacterial enzymes. Materials & methods: Series 5 (5a-5j) and Series 9 (9a-9t) compounds were synthesized and characterized using spectroscopic techniques. Their antimicrobial and antitubercular activities were evaluated against Mycobacterium tuberculosis, Staphylococcus aureus, Bacillus subtilis, and E. coli. IC50 values were determined, and molecular docking studies were conducted to assess binding interactions with M. tuberculosis enoyl-ACP reductase (InhA) and E. coli DNA gyrase B. Results: Series 5 compounds exhibited moderate activity, with 5f, 5 g, 5i, and 5j showing notable inhibition. Series 9 derivatives displayed superior dual-target inhibition, with 9t, 9c, 9a, 9b, and 9p achieving >90% inhibition against S. aureus and B. subtilis. The lowest IC50 against M. tuberculosis was observed for 9c (1.50 mu g/mL), followed by 9a (2.84 mu g/mL) and 9b (2.73 mu g/mL). Molecular docking confirmed strong binding interactions, correlating with observed biological activities. Conclusions: Series 9 compounds, particularly 9t, 9c, and 9a, demonstrate high potential as dual-target antimicrobial drug candidates. Further optimization may enhance their therapeutic efficacy. [GRAPHICS]
Keywords: Antimicrobial activity; antitubercular agents; Coumarin derivatives; Molecular docking studies; structure-activity relationship (SAR); thiophene-based compounds